É preciso falar, superando o silêncio e a indiferença: a experiência poético-musical no combate ao racismo - Medeiros, Shirley Aires de (2023)
The poetic-musical experience in the fight against racism served as a practical basis for the research addressed in this article. This experience was developed as mediation through pedagogical workshops whose central purpose was to raise awareness and problematize the racism that, in Brazil, discriminates and marginalizes on a large scale those with more evident African ancestry. Based on examples of the repertoire produced on the theme of black identity movements (in genres of marginal poetry, such as rap and slam) and the aesthetics cultivated by young segments of our time (the case of hip-hop culture, at the beginning of the 21st century), an attempt was made to dimension the Art curricular component (Music) observing expectations foreseen in the legal frameworks that deal with the recognition and appreciation of African and Afro-Brazilian history and culture, contributing to articulate in the curricular and institutional space an environment that stimulates the adoption of postures and actions to combat racism, supported by normative documents, among which the National Curriculum Guidelines for the Education of Ethnic-Racial Relations stand out, defined based on Law Nº 10,639/2003. The research was carried out within the scope of the Professional Master's Program in Arts in National Network (PROF-ARTES) / Federal University of Paraíba, Campus I, João Pessoa, with the participation of students from a public school, in a neighborhood on the outskirts of the capital from the state of Paraíba.